2021
DOI: 10.48550/arxiv.2103.12442
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

On Stability of Asymptotically Free Mimetic Hořava Gravity

Tobias B. Russ

Abstract: Asymptotically free mimetic gravity has been introduced as a proposal for a classical limiting curvature theory with the purpose of singularity resolution. It was found that in a spatially flat universe an initial stage of exponential expansion with graceful exit is a generic consequence, regardless of the matter content. In this work I will analyze stability of cosmological perturbations in such a model, considering only the degrees of freedom of pure mimetic gravity. I show that the addition of Hořava-gravit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Moreover, mimetic theory can investigate the flat rotation curves of spiral galaxies without the need of dark matter [14,15]. From a cosmological point of view, the theory of mimetic has discussed a lot of interesting research papers in the past few years [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and black holes physics [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. It has been shown that for a spherically symmetric spacetime the only solution is the Schwarzschild spacetime which means that the Birkhoff's theorem is hold.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, mimetic theory can investigate the flat rotation curves of spiral galaxies without the need of dark matter [14,15]. From a cosmological point of view, the theory of mimetic has discussed a lot of interesting research papers in the past few years [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] and black holes physics [35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53]. It has been shown that for a spherically symmetric spacetime the only solution is the Schwarzschild spacetime which means that the Birkhoff's theorem is hold.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been shown that this theory can explain the flat rotation curves of spiral galaxies without needing to particles DM [10,11]. Mimetic theory of gravity has arisen a lot of enthusiasm in the past few years both from the cosmological viewpoint [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30] as well as black holes physics [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49][50]. The investigations on the mimetic theory of gravity were also generalized to f (R) gravity [51][52][53][54][55][56][57][5...…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been demonstrated that mimetic theory can explore the coherent rotational patterns observed in spiral galaxies without relying on the existence of dark matter particles [13,14]. Lately, there has been a significant surge of enthusiasm surrounding the cosmological framework due to the emergence of the mimetic theory [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] and black holes physics [33][34][35][36][37][38][39][40][41][42][43][44][45][45][46][47][48][49][50][51]. The theory has further extended its scope to include f (R) mimetic gravity, incorporating additional insights and explanations [52][53][54][55][56][57][58][59]…”
Section: Introductionmentioning
confidence: 99%